2020
DOI: 10.14218/jcth.2019.00054
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Assessing Burden in Caregivers of Patients with Cirrhosis

Abstract: Background and Aims: Being a caregiver for a patient with chronic liver disease (CLD) can be burdensome mentally, emotionally financially, and physically. The aim of this study was to systemically review the available tools and propose tools that can comprehensively evaluate caregiver burden for individuals caring for patients with CLD. Methods: We searched the PubMed database for all studies on the impact of patients with CLD on caregiver burden without timeframe restriction. Eligible studies included cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…We did not find an association between frailty and caregiver burden, which is divergent from previous work in a community-dwelling geriatric population, which showed that frailty, defined by FFI ≥ 3, was associated with caregiver burden, measured by ZBI-12 [35]. One might expect that frailty is associated with higher caregiver burden, given the likely increased demands on the informal caregiver, but the ZBI-12 may not provide a complete assessment of caregiver burden as it does not assess other domains, such as the impact of financial stress on caregiver burden [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find an association between frailty and caregiver burden, which is divergent from previous work in a community-dwelling geriatric population, which showed that frailty, defined by FFI ≥ 3, was associated with caregiver burden, measured by ZBI-12 [35]. One might expect that frailty is associated with higher caregiver burden, given the likely increased demands on the informal caregiver, but the ZBI-12 may not provide a complete assessment of caregiver burden as it does not assess other domains, such as the impact of financial stress on caregiver burden [36].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived social support scores, based on ISEL-12, were fairly high; the median overall social support score was [31][32][33][34][35][36]. No association was found between patient gender, age, race/ethnicity, BMI, etiology of liver disease, decompensated disease, or MELD-Na and ISEL-12.…”
Section: Caregiver Burdenmentioning
confidence: 89%
“…[25][26][27][28][29] Caregivers of patients with DC report feeling unprepared to provide physical care, medication management, and transportation to their loved ones and often experience significant financial burdens . [23][24][25]27,[30][31][32] Importantly, the financial, social, and psychological burdens of cirrhosis experienced by caregivers can continue to impact caregivers after patients die.…”
Section: The Role Of Caregi Vers In Palli Ati Ve Carementioning
confidence: 99%
“…[14] This figure also includes patients, families, and the multidisciplinary team as central to palliative care Aspe cts of Care under-recognized psychological, physical, and financial burdens. [22][23][24][25][26][27] Their symptoms include stress, anxiety, depression, insomnia, decreased health-related quality of life (HRQoL), and worse physical health. [23,[25][26][27] Psychological symptom burden among caregivers is associated with patients' alcohol use, encephalopathy, ascites, liver disease (LD) severity, repeated hospitalizations, prognostic uncertainty, and lack of information.…”
Section: The Role Of Caregi Vers In Palli Ati Ve Carementioning
confidence: 99%
“…68,69 The 22-item version is the most widely used version, but shorter versions of the ZBI have also been developed, including a 6-item version that has good diagnostic utility. 69,70 The ZBI has been validated in caregivers of patients with heart failure, 71 cirrhosis, 72 and used in studies of caregivers of renal transplant recipients 73 and patients with interstitial lung disease. 74 Given the unique pressures faced by caregivers of transplant patients, development and validation of caregiver burden screening tools tailored to solid organ transplant populations are needed.…”
Section: Screening For Caregiver Burdenmentioning
confidence: 99%